Evolution, And Phylogeny Of Herv-S Family In Some Closely Related Primates - Najmalddin, Hawnaz Othman; Taher, Aso Ahmed; Mohammed, Shad Arif (Sulaimani Journal for Pure and Applied Sciences, 2015)
Human endogenous retroviral element S-family (HERV-S) has been present within the human genome as well as various closely related primates. The expression pattern, copy number, chromosomal locations of the proviral element have been extensively studied. Here, we analyse the pol fragment of the HERV-S in human tissues, cancer cell lines and in seven other related primates. Phylogenetic analysis of the HERV-S pol gene suggests division of the family into two groups among the tested species that have arisen throughout the primate evolution by gene duplication as well as other genetic alterations. Also, the tree analysis of human tissues and cancer cells suggest that expression of the chromosome X pol fragment is identical to expression of the pol fragment in cancerous cells more than its relation to the pol sequence on other human chromosomes. To sum up, our data provide a clarification about the dynamic evolutionary characteristics as well as phylogenetic relationships of HERV-S family pol gene in primates.
Keywords: HERVS; Endogenous; Phylogeny; Evolution; Primate; Cancer cell line